The low-temperature radial thermal expansion of single-walled carbon nanotube bundles saturated with nitrogen - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Popov, S.N.; Vinnikov, N.A.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The effect of a N2 impurity on the radial thermal expansion coefficient αr of single-walled carbon nanotube bundles has been investigated in the temperature interval 2.2–43 K by the dilatometric method. Saturation ofnanotube bundles with N2 caused a sharp increase in the positive magnitudes of αr in the whole temperature range used and a very high and wide maximum in the thermal expansion coefficient αr(T) at T ~ 28 K. The lowtemperaturedesorption of the impurity from the N2-saturated powder of bundles of single-walled carbon nanotubes with open and closed ends has been investigated.